Approach Geography in Environmental Research (For example, Nghe An province) - Thuy, Hoang Luu Thu (Vietnam Journal of Earth Sciences, 2014)
Landscape Ecology has diversity function, including the natural function of landscapes, ecological function of ecosystems with economic - society function is the basis of economic - social activities of the human. Therefore, landscape ecology is considered as territorial of ecology environment - human habitat. By approaching landscape ecology assessment through the evaluation of natural - social economic - environmental function that landscape ecology can undertake, environment function analysis of landscape ecology has been conducted, from that to establish the map of the environmental function of Nghe An, scale 1/100.000. There were 5 regions with 14 sub-regions of environmental function have been shown in the map. The proposed layout-oriented of development activities on the territory of Nghe An province according to plan in 2020 to conform to the environmental function in each region and sub-region as an application with high scientific and practical basis in using environmental function zoning map to research and develop environmental protection plan of Nghe An province